PERANAN MODEL PEMBELAJARAN KOOPERATIF TIPE SCRAMBLE TERHADAP MINAT BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPS DI KELAS III SD ISLAM DATOK SULAIMAN PALOPO - Kartila Kartila (Fakultas Tarbiyah dan Ilmu Keguruan, 2019)
This study aims to determine the implementation of scramble type cooperative learning models and to find out the learning interests of students who apply the model and to know the supporting factors and obstacles to the implementation of scramble type cooperative learning models in increasing student interest in social studies in Grade III Islamic Elementary School Datok Sulaiman Palopo. This study uses a type of qualitative descriptive research carried out in class III Islamic Elementary School Datok Sulaiman Palop. Data collection techniques used were observation, interviews, and documentation. The results of this study indicate that the implementation of a scramble type cooperative model makes students directly active in learning activities